CD4 T Cell Depletion at the Cervix during HIV Infection Is Associated with Accumulation of Terminally Differentiated T Cells - Gumbi, P. P. (American Society for Microbiology, 2011)

(untitled)
In blood, the accumulation of terminally differentiated (TD) T cells during HIV infection is associated with CD4 T cell loss and HIV disease progression. Here, we investigated the maintenance and functional characteristics of memory T cells at the cervix. We found that CD4 T cell depletion at the cervix mirrors CD4 depletion in blood. In all women, depletion of CD4 T cells at the cervix was associated with significant reductions in CD45RA(−) CCR7(+) (central memory [CM]) T cells and the accumulation of CD45RA(+) CCR7(−) (TD T cells). We determined whether inflammation in the genital tract was associated with the local differentiation of T cells at the cervix. In uninfected women, genital tract inflammation was associated with the accumulation of CD45RA(−) CCR7(+) CM CD4 T cells and reduced frequencies of CD45RA(+) CCR7(−) TD cells at the cervix. This finding may reflect the fact that, in the absence of HIV infection, TD T cells may be slowly lost in the presence of genital inflammation, while CD45RA(−) CCR7(+) CM T cells are recruited to replenish the diminishing CD4 T cell pool. Following global stimulation with phorbol myristate acetate (PMA)-ionomycin, we noted a significant interleukin 2 (IL-2) deficit in both cervical and blood CD4 T cells from HIV-infected women compared to uninfected women, while gamma interferon (IFN-γ) production was similar, irrespective of HIV status. Few HIV-infected women had detectable IFN-γ and IL-2 HIV-specific T cell responses at the cervix, and these responses were significantly lower in magnitude than the corresponding responses in blood. These data suggest that CD4 depletion was associated with the accumulation of terminally differentiated T cell phenotypes at the cervical mucosa defective in their ability to produce IL-2. CD4 depletion and compromised immunity at the cervix may be accompanied by progressive decline of central memory-like T cells and development of T cells toward terminally differentiated phenotypes.